PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA TEKNIK BULU TANGKIS YANG BERBASIS APLIKASI MACROMEDIA FLASH - Taufiq Hidayat (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Basic techniques of badminton games are: 1.Racket handling 2. Types pf services 3. Types of upper hit. 4. Types of lower hit. Basic techniques is an important thing to advance the students’ college for badminton school subject. Therefore, it should be learned before to build up the skill off basic technical of badminton games. This research uses and development methodology (R&D). This steps of how to advance an interactive learning media for the techniques of badminton game is based on flash macromedia application by Bord and Gall model. Kevali and media is obtained from the result of professional validation from both of two media and two materials proffesionals.The result of the first professional material is about 91.66% and media professional is about 92% by criteria “properly used” The practical of media is obtained through by the class A academic 2022-2023 of the students’ college quessioner in sports’ faculty which is about 97.5% by the criteria “properly used”.The conclusion is interactive learning media of techniques in badminton game based on the flash macromedia application is valid and practical to be used in techniques of badminton game.